Audiovisual translation tools for the assessment of hard of hearing students - Ana María Hornero Corisco; Pilar González-Vera (Universitat Jaume I. Department of English Studies, 2020)
The Spanish University requires all its students to reach a specific level in a foreign language, as part of the requisites to obtain their degrees. At present, there is a lack of homogeneity in the criteria set for the assessment of hard of hearing students' skills. A preliminary survey reveals the current measures applied in a number of Spanish universities. Our suggestion is that a uniform listening test should be implemented for hard of hearing students. The main goal of our research was to check what kind of test is more adequate for these students. For that purpose, several hard of hearing students did different listening activities using audiovisual materials that had been previously edited and adapted to their special needs. They also responded to different question tasks: multiple-choice, true/false, gap-filling. The results throw some light on the type of test format that should be used with the hard of hearing community.